The Use of Chipless Sensors With Rfid for Condition Monitoring - Biliç, H. Gökay; Büyüköztekin, Tarık; Büyüköztekin, Tarık; Özdemir, Serhan; Özdemir, Serhan (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper presents the development phases and overview of developing research in the area of RFID condition monitoring, focusing on chipless sensors especially use in strain and temperature sensing applications. Classification of RFID sensors and smart material fundamentals are reviewed. The compact and feasible design of RFID sensors will be considered, as well as with the effect of different material usage. Finally, the use of chipless sensors with different condition monitoring applications and their challenges are investigated.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Chipless sensors; Radio frequency identification; Tags; Condition monitoring; Strain